NON-LINEAR TRANSFORMATION OF SIGNALS IN SOFTWARE DESIGN OF DIGITAL CONTROL SYSTEMS COMPLEX (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
Dependencies between signals and dependence of signals on time are strictly non-linear. Non-linear elements, commonly used in the synthesis of automatic control systems, include: a two-point link, a two-point link with hysteresis, a three-point link, a three-point link with hysteresis, a module, saturation with insensitivity.